Pengaruh inovasi produk, social media terhadap keunggulan bersaing pada umkm cafe dipontianak - Arweni Ibrahim; Thea Geneveva J.J; Muchammad Ariffin (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2023)
Culinary UMKM also has a strategic role in strengthening the identity of the Indonesian nation. The elements of creativity in the culinary subsector are presented in terms of presentation, aesthetics, and local culture that encourages the taste so that it attracts public interest in buying.Product innovation is a step for entrepreneurs to be able to continue in the opportunity to maintain by applying the strategy of innovation in pandemic times such as this makes UMKM entrepreneur must innovate towards its product because innovation can give plus value to the product itself so that it can attract the attention of the consumers. UMKM enterprises can more freely promote social media than to take advantage of momentum, promotional measures in social media are also cheaper and more targeted. Social media can direct entrepreneurs to target markets that are appropriate according to age, and location, adapted to the products sold. This research is a type of survey using a questionnaire to the perpetrators of UMKM Kuliber cafe in Pontianak with several respondents of as many as 60 people under purposive sampling. The analytical method used was WarpPLS 6.0 in the SEM-PLS model testing. The results of this research showed that product innovation has a significant influence in terms of competitive advantage, and social media has a significant impact on competitive advantages